Design, Semisynthesis, and Estrogenic Activity of Lignan Derivatives from Natural Dibenzylbutyrolactones - Priscila López-Rojas; Ángel Amesty; Miguel Guerra-Rodríguez; Yeray Brito-Casillas; Borja Guerra; Leandro Fernández-Pérez; Ana Estévez-Braun (MDPI AG, 2022)
Based on molecular docking studies on the ERα, a series of lignan derivatives (3-16) were designed and semisynthesized from the natural dibenzylbutyrolactones bursehernin (1) and matairesinol dimethyl ether (2). To examine their estrogenic and antiestrogenic potencies, the effects of these compounds on estrogen receptor element (ERE)-driven reporter gene expression and viability in human ER+ breast cancer cells were evaluated. Lignan compounds induced ERE-driven reporter gene expression with very low potency as compared with the pure agonist E2. However, coincubation of 5 μM of lignan derivatives 1, 3, 4, 7, 8, 9, 11, 13, and 14 with increasing concentrations of E2 (from 0.01 pM to 1 nM) reduced both the potency and efficacy of pure agonists. The binding to the rhERα-LBD was validated by TR-FRET competitive binding assay and lignans bound to the rhERα with IC50 values from 0.16 μM (compound 14) to 6 μM (compound 4). Induced fit docking (IFD) and molecular dynamics (MD) simulations for compound 14 were carried out to further investigate the binding mode interactions. Finally, the in silico ADME predictions indicated that the most potent lignan derivatives exhibited good drug-likeness.